Profil Awal Keterampilan Proses Sains Siswa pada Materi Makhluk Hidup dan Lingkungannya - Retno Susanti; Bowo Sugiharto; Baskoro Adi Prayitno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The development of science and technology until the 21st century is inseparable from skills that begin withbasic skills to observe a phenomenon and then continue with more complex skills. This skill is called scienceprocess skills. The research conducted is qualitative descriptive with the aim of classifying the science processskills of students. The subjects of the study are 35 students of class X-A SMKN 2 Sukoharjo for the 2024/2025academic year. Data collection was carried out through a science process skills test for science subjects. Thescience process skills test instrument includes 11 indicators consisting of 20 multiple-choice test items. Theanalysis was carried out on the results of the students' tests on each indicator and categorized into five categoriesof science process skills consisting of very good (SB), good (B), medium (S), poor (K), and very poor (SK).The results of the study showed that the average score of the highest science process skill indicator was obtainedin the classification indicator, which was 55 with the category of less (K). The indicator defines operationallyand makes a hypothesis that it has the lowest average score of 27 with a very poor category (SK). Based onthese results, it is evident that students' science process skills still need to be trained so that they can beimproved. So, teachers need to implement meaningful science learning in order to improve students' scienceprocess skills.